(untitled) (Studia Prawnicze / The Legal Studies, 2000)
Kodeks etyki lekarskiej nie jest aktem prawnym; wskazuje na to interpretacja przepisów art. 1 i art. 5 k.e.l. Mimo to jednak powinien być uwzględniony w procesie stosowania prawa, jego wykładni, w szczególności teleologicznej i mieć wpływ na tworzenie nowych rozwiązań prawnych. The Code of Medical Ethics is not a legal act; this is indicated by the interpretation of the provisions of Articles 1 and 5 of the Code of Medical Ethics. Nevertheless, it should be taken into account in the process of applying the law, interpreting it, in particular teleologically, and influencing the creation of new legal solutions.